2021
DOI: 10.3389/fmicb.2021.642422
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Across Scales: A Holistic Modeling Framework Integrating Laboratory and Field Studies for Microbial Ecology

Abstract: Over the last century, leaps in technology for imaging, sampling, detection, high-throughput sequencing, and -omics analyses have revolutionized microbial ecology to enable rapid acquisition of extensive datasets for microbial communities across the ever-increasing temporal and spatial scales. The present challenge is capitalizing on our enhanced abilities of observation and integrating diverse data types from different scales, resolutions, and disciplines to reach a causal and mechanistic understanding of how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 118 publications
0
23
0
Order By: Relevance
“…We selected 110 bacterial isolates from the same ORFRC field site for this study and compared the growth of the isolates in both NLDM and R2A. Notably, most isolations (35%) were made using R2A ( Supplementary Table 3 ; Thorgersen et al, 2015 ; Hemme et al, 2016 ; Liu et al, 2018 ; Price et al, 2018 ; Carlson et al, 2019 ; Vuono et al, 2019 ; Lui et al, 2021 ). It was found that only 2 out of the 110 isolates did not display significant growth in NLDM, whereas 6 out of the 110 isolates did not display significant growth in R2A medium ( Figure 1 and Supplementary Tables 3 , 7A–C ).…”
Section: Resultsmentioning
confidence: 99%
“…We selected 110 bacterial isolates from the same ORFRC field site for this study and compared the growth of the isolates in both NLDM and R2A. Notably, most isolations (35%) were made using R2A ( Supplementary Table 3 ; Thorgersen et al, 2015 ; Hemme et al, 2016 ; Liu et al, 2018 ; Price et al, 2018 ; Carlson et al, 2019 ; Vuono et al, 2019 ; Lui et al, 2021 ). It was found that only 2 out of the 110 isolates did not display significant growth in NLDM, whereas 6 out of the 110 isolates did not display significant growth in R2A medium ( Figure 1 and Supplementary Tables 3 , 7A–C ).…”
Section: Resultsmentioning
confidence: 99%
“…Microbial processes in soil are complicated by the physically and chemically structured environment, which is characterized by the porous soil architecture, diverse components and interfacial properties, coupled with the heterogeneous distribution of water, solutes, gases, and microbes. ,, Mechanistic understanding of the diversity, functions, and global ecological significance of soil microbes are still lack . Microfluidics is rapidly transforming the study of microbiology. Multiple features make microfluidics a promising technology for exploring soil microbial processes .…”
Section: Microfluidics For Investigating Soil Microbial Processesmentioning
confidence: 99%
“…The microenvironments, such as temperature, oxygen, flows, and chemical gradients, can be precisely manipulated as being constant or oscillating, homogeneous or heterogeneous. Therefore, microfluidics can serve as an experimental platform that addresses the challenge to link field (in situ) experiments and conventional laboratory culture-based methods for microbial studies . In this section, we review how soil microbial processes on-a-chip platforms facilitate soil microbiology studies from three aspects: (1) Microbe-environment interactions, which mainly deal with the question of how soil microbes adapt to environmental factors and how microbial activities reshape the soil environments; (2) Microbe-microbe interactions, which occur in microbial communities; and (3) Microbe-plant interactions, which dominate the processes in the rhizosphere.…”
Section: Microfluidics For Investigating Soil Microbial Processesmentioning
confidence: 99%
“…The existence of abundant metal resistance genes in Rhodanobacter strains has been demonstrated by metagenomic data of the ORR site groundwater samples ( 8 ). As most studies have been based on metagenomic sequencing, studies with culture-dependent methods (i.e., isolation and growth) are needed to understand the growth, physiology, and mechanisms of adaptation for discrete but related populations ( 9 ).…”
Section: Introductionmentioning
confidence: 99%